HUBUNGAN KEKUATAN OTOT LENGAN DAN BAHU DENGAN ACCURACY SMASH PADA TIM VOLI PUTRI SRIKANDI PEKANBARU - Marlina, Dewi Marlina; Agust, Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:Problems encountered in Women Volleyball Team Heroine is the result of unsatisfactory accuracy smash that followed the match has not achieved good results. One of the factors that lead to less successful in doing smash accuracy is the arm and shoulder muscle strength less than the maximum, due strenght less so in the smash less focused and less good so the results are not satisfactory. This research is done by using a correlation study design aims is to investigate how far the variables in a factor associated with lain.korelasi factor is a study designed to determine the level of relations of the different variables in a population that aims to find out how great contribution between independent variables and the dependent variable. (Arikunto, 2006: 131). Population is the whole object of research. The population in this study is the women's volleyball team were present and active in the team pekanbaru heroine is 13 people.To obtain research data used Expanding Dynamometer tests for shoulder arm muscle strength, and smash Accuracy tests for accuracy.data are obtained in the analysis with a simple product moment correlation. Based on the analysis of data obtained koifisien correlation of rhitung = 0.616> of rtabel = 0.576. thus Ha Ho accepted and rejected. This means that there is a relationship between strenght muscle arms and shoulders with accuracy smash, where the provisions of the correlation of a variable with other variables determined from rhitung> rtabel, dansignifikan (Sugiyono, 2008: 258).Keywords: Shoulder Arm Muscle Strength, Accuracy Smash, Volleyball